Modifikasi Servo Drive MR-J2S-350A pada Panel Utama Mesin Building IMC 05 MC 02 dengan Menggunakan Servo Drive MR-J4-350A - Sadewa, Fakhri; Siahaan, Paul Michael (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2024)
AFG is a manufacturing company that produces various kinds of motorcycle tires. In the production process PT. AFG has several processes, one of which is the assembly process. In this process where several components such as tread, bead, ply, and IB are combined. Thus, the output of this assembly process is a green tire. The assembly here uses a BTU (bladder turn up) type machine, more precisely on the IMC.05.MC.02 engine. On this machine there are several problems that cause production to be disrupted due to this problem. The cause of this problem is that the components used have decreased in performance because they have been installed for years (obsolete) and also the components have been produced again so modifications are made. After being modified where to increase the type of servo drive which originally used the MR-J2S to use the servo drive with the MR-J4 type. After this modification was made on the IMC 05 MC 05 engine where previous problems such as engine errors etc. had disappeared or there were no the same problems so the machine can produce smoothly without any error.